Multilevel DC-AC Converter Interface with Solar Panels - Yue Cao (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
This paper presents a single-phase 11-level (5 H-bridge) cascaded multilevel DC-AC converter that has implemented a Phase Locked Loop (PLL) and Maximum Power Point Tracking (MPPT) with 5 separate solar panel DC sources. This topology upgrades the conventional 3-level Pulse Width Modulation (PWM) controlled converter with advantages such as smoother output waveforms, more flexibility in voltage range, smaller filter size, and switching angle control. Simulation results of voltage synchronization using PLL and experimental setup and results implementing the entire converter interface are also presented.
Keywords: Undergraduate Research; Pursuit